DESAIN TARI PIRING LENGGOK SI ANAK DAGANG KOREOGRAFER ISKANDAR MUDA - Riska Fitrianisa (Universitas Negeri Medan, 2016)
Trade sianak plate swing dance is one dance originating from the Minangkabauthat developed in the city of Medan. The purpose of this study is to discuss theswing sianak Plate Dance Choreographers Trade Iskandar Muda views fromForm, Top Design, Design Floor.In the discussion of this study used the theories related to the topic of study suchas the Theory of Forms of Sal Murgiyanto Dance, Top of the Design Theory andDesign Theory Sudarsono floor of La MeriWhen the study to discuss Plate Dance Dance Choreographer swing sianak TradeIskandar Muda was conducted for two months. Place of research conducted at theStudio Dance Medan State University Faculty of Language and Art jl. IskandarWilliam. Data collection techniques including observation, interviews, literaturestudies and doumentasi, which is then analyzed by qualitative descriptive method.Based on the results of research conducted showed that dance Lenggo plate sianakthis trade is a dance that takes the movements of the Minang community activitiesare generally farmers, and developed into a new creation dance. There aremovements born / inspired by the movements of the flora, fauna and koreomatik.Form of motion which is divided into three energy intensity (weak, medium,strong), space (small and large), and time (slow medium, fast). There are 8 designon frequent / dominant in this dance that Spiral design, symmetrical,asymmetrical, curved, delayed, flat, low, and advanced. There are two designs onthe dance floor that occurred of which this is the floor design of straight lines andcurved lines flooring design. This dance had several times shown by the studiowidatra overseas parts of Asia and Europe, namely: Performance CompetitionCultural North Sumatra on